The features of state changes of proteinase- inhibitory system in the lungs of guinea pigs in the early period of experimental bronchial asthma - M. S. Regeda; M. A. Kolishetska; N. G. Sementsiv; M. L. Baida (Kazimierz Wielki University, 2015)
Reheda M. S., Kolishetska M. A., Sementsiv N. G., Baida M. L. Особливості зрушень стану протеїназо-інгібіторної системи в легенях морських свинок у ранньому періоді експериментальної бронхіальної астми = The features of state changes of proteinase- inhibitory system in the lungs of guinea pigs in the early period of experimental bronchial asthma. Journal of Education, Health and Sport. 2015;5(11):419-426. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34232 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A419-426 https://pbn.nauka.gov.pl/works/672064 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 24.11.2015.   УДК: 612.24:616.248-039.11-092.9]:577.15024/.025   Особливості зрушень стану протеїназо-інгібіторної системи в легенях морських свинок у ранньому періоді експериментальної бронхіальної астми The features of state changes of proteinase- inhibitory system in the lungs of guinea pigs in the early period of experimental bronchial asthma   М. С. Регеда, М. А. Колішецька, Н. Г. Семенців, М. Л. Байда M. S. Reheda, M. A. Kolishetska, N. G. Sementsiv, M. L. Baida   Львівський національний медичний університет ім. Данила Галицького Danylo Halytskiy Lviv National Medical University   Article The gradual increase of contents of the azoalbumin, azokasein and azokolagenhas been established in the research already in the early period of forming of experimental bronchial asthma (BA). So, we are observing the increase of indicators of azoalbumin in the early period of the development of BA (on the 5th,19th day ), accordingly on 31,8%(p≤0,05) and 42,4% (p≤0,05) in comparison with control group. The similar tendency of changes was discovered during the research of the level of azokasein, which also were increasing in the conditions of the development of BA, as on the 5th day by 45,1% (p≤0,05), so on the 19th day of the experimental model of the disease by 51,25% (p≤0,05) in comparison with the group of intact animals. Similar data were obtained in the early period of bronchial asthma according to the contents of azokolagen. Its increase by 50% (р ≤0,05) and 58,3% (р ≤0,05) was discovered in comparison with the control in condition of forming of this pathology. The investigation of protein inhibitors, in particular, α1-protease inhibitor (α1-IP) in the early period of the experiment has showed its slight increase by 14,7%(р≤0,05) in comparison with the first group of animals on the 5th day of the experiment, that may prove about the inclusion of compensatory mechanisms of protection of proteinase-inhibitory system. However, on the 19th day of the experimental BA, the indicators α1-IP is located on the level of control quantities (р≤0,05). In relation to the activity of the α2-macroglobulin in the lungs on the researched days of the experimental BA, it is increasing by 29,7% (р≤0,05) on the 5th day and it doesn't suffer significant changes on the 19th day of the experiment in comparison with the group of the intact guinea pigs (р≤0,05). Therefore, our researches of biochemical indicators of proteinase-inhibitory system in the lungs discovered the increase of proteolytic activity on the background of insufficient marked compensatory mechanisms of protein inhibitors with advantage of damage mechanism over  protection mechanisms in the early period of the development of experimental model BA. Key words: asthma, proteinase-inhibitory system.   Реферат У роботі встановлено поступове зростання вмісту азоальбуміну, азоказеїну та азоколагену вже в ранній період формування експериментальної бронхіальної астми (БА). Так, спостерігаємо підвищення показників азоальбуміну в легенях у ранній період розвитку БА (5-а, 19-а доби) відповідно на 31,8% (р ≤0,05) і 42,4% (р ≤0,05)  в порівнянні з контрольною групою.  Аналогічний напрям змін виявлено під час дослідження рівня азоказеїну, який також зростав за умов розвитку БА , як на 5-у добу на 45,1% (р ≤0,05), так і на 19-у добу цієї експериментальної моделі хвороби на 51,25% (р ≤0,05) в порівнянні з групою інтактних тварин. Подібні дані одержані в експерименті в ранньому періоді бронхіальної астми щодо вмісту азоколагену. Встановлено його зростання відповідно на 50% (р ≤0,05) і 58,3% (р ≤0,05)  в порівнянні з контролем за умов формування цієї патології. Дослідження білкових інгібіторів, зокрема, α1-інгібітора протеаз (α1-ІП) в ранні терміни експерименту показало його незначне зростання на 14,7% (р≤0,05) в порівнянні з І групою тварин на 5-у добу експерименту, що може свідчити про включення компенсаторних механізмів захисту протеїназо-інгібіторної системи. Проте, вже на 19-у добу експериментальної БА показники α1-ІП знаходяться на рівні контрольних величин (р≤0,05). Щодо активності α2-макроглобуліну в легенях  на досліджувані доби експериментальної БА, вона підвищується на 29,7% (р≤0,05) на 5-у добу і не зазнає достовірних змін на 19-у добу експерименту в порівнянні з групою інтактних морських свинок (р≤0,05).